Explorations on the accountability of independent regulatory agencies - Korkmaz, Gizem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2009., 2009)
This thesis aims at analyzing in a game theoretical framework the behavior of a regulator to be appointed by a government that may follow an objective different than the (social) objective that was used at the initial regulatory-design stage. More specifically, the thesis is centered around analyzing the trade-off between independence and accountability of a regulatory authority to be appointed by politically-biased governments subject to reelection, and it aims to contribute to the regulatory design literature by analyzing the performance of an independent regulatory authority subject to differing degrees of accountability under these circumstances. Analyzing the optimal contracts for the games studied, we show how the level of corruptibility of the agency affects the optimal level of investigation to be taken. Certain amount of accountability is necessary to reach the optimum as long as the regulator is not benevolent. However, we find that the politically polarized government can use the accountability as a tool to benefit a certain group in the economy by distorting the output level and hence the social welfare.
Keywords: Independent regulatory commissions.; Game theory.